Adhezní limity procesu trakce a brzdění - Čáp, Jaroslav (Univerzita Pardubice, 2001)
The paper deals with significant differences, dissimilarities and operating influences during the traction and braking process of railway vehicle. The mentioned factors are displayed in the reached values of adhesion coefficient as well as relative slip. The possibilities of theoretical and experimental investigation of adhesion mechanism and mutual correlation of both these processes are in search.
Keywords: kolejová vozidla; brzdění; trakce; adheze; skluzové síly